2007
DOI: 10.1021/jp0674524
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Methanol in Zeolite NaY:  A Molecular Dynamics Study

Abstract: Molecular dynamics simulations were performed in order to obtain a detailed understanding of the self-diffusion mechanisms of methanol in the zeolite NaY system. We derived a new force-field term to describe the interactions between the methanol molecules and the extraframework cations. From the simulations, we show that diffusive behavior in the high-temperature range consists of a combination of both short- and long-range motions at low and intermediate loadings. This type of motion is characterized by an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…For example, for methanol in a NaY system, theoretical investigations showed that methanol facilitates migration of the Na + cation from the vicinity of the active site to the center of the pore, which influences the stability of the methanol cluster. 65 The stability of the solvated cation in the center of the pore, surrounded by methanol molecules, may be due to a favorable electrostatic environment as well as the distance of the methanol cluster from the active site hindering the retransfer of the Brønsted proton from the methanol. Theoretical studies of gas-phase methanol reported that the energy to form a methanol cluster, protonated or neutral, reaches a plateau after adding five methanol molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for methanol in a NaY system, theoretical investigations showed that methanol facilitates migration of the Na + cation from the vicinity of the active site to the center of the pore, which influences the stability of the methanol cluster. 65 The stability of the solvated cation in the center of the pore, surrounded by methanol molecules, may be due to a favorable electrostatic environment as well as the distance of the methanol cluster from the active site hindering the retransfer of the Brønsted proton from the methanol. Theoretical studies of gas-phase methanol reported that the energy to form a methanol cluster, protonated or neutral, reaches a plateau after adding five methanol molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The charges for methanol were obtained by a Mulliken population analysis of ab initio DFT calculations by Blanco and Auerbach [52]. These parameters were scaled by Plant and associates [53] to attain a more polarized methyl group corresponding to methanol at acidic sites in zeolite frameworks. Methanol intramolecular harmonic potentials for covalent bonds, angles, and dihedrals were determined using ab initio DFT calculation at the quadratic configuration interaction calculation with single and double excitations (QCISD) level of theory to attain the ground state energy and electron density distribution [52].…”
Section: Interatomic Potentialsmentioning
confidence: 99%
“…(2). Both bonded and non-bonded potential parameters were taken from the work of Plant et al [14] for methanol diffusion in the NaY zeolite as listed in Tables 1 and 2. The validity of these force field parameters was confirmed by an agreement of the diffusion coefficient of methanol obtained in the liquid phase by simulation to be 1:365 Â 10 À9 m 2 s À1 at an ambient temperature with the corresponding experimental results of 1:3 Â 10 À9 m 2 s À1 [15].…”
Section: Model and Simulationsmentioning
confidence: 99%